A spatial analysis of villagers\' satisfaction with services provided by Rural Water and Wastewater Company (A case study of Fazl Dehestan, Neyshabur County) - Hamdollah Sojasi qidari; Hamide Mahmoodi; Hoori havvaei (تحقیقات کاربردی علوم جغرافیایی)
Higher quality of services provided in the rural areas requires feedback, consulting with villagers, and their active participation in rural development process. Water services are one of the most basic services provided in rural areas. Accordingly, the present study seeks to evaluate the satisfaction level of rural residents with the quality of services provided by Rural Water and Wastewater Company. This study was conducted in a descriptive-analytical method, and the population was comprised of 132 households randomly selected from rural residents living in rural areas of Central District of Neyshabur County with an acceptable reliability score. Investigating the relationship between the five dimensions of the study and the individual characteristics indicates that there is a significant relationship between age, gender and education level and satisfaction with quality of the services in sample villages. At the same time, assessing the satisfaction with the quality of water services in sample villages indicates that the quality of water services in sample villages is at a satisfactory level. The analytical results of the confirmatory factor analysis of the research indicators showed the highest percentage of variance of the research dimensions belonged to 'empathy', with 30.91% and the least value of variance belongs to ‘tangible changes’ (21.28%). The spatial analysis of villagers' satisfaction with drinking water supply services in sample villages showed that the village of Sheikhlan with 103.10 Qi had the highest satisfaction level, and the village of Turani with 0.990 Qi had the least satisfaction with the quality of services..